Fatigue performance of prestressed concrete beams using BFRP bars. (30th December 2017) - Younes, Taha; Al-Mayah, Adil; Topper, Tim
Highlights: Basalt bars were used in prestressing concrete beams subjected to fatigue loading. There was little effect of prestressing on fatigue strength for low fatigue lives. Enough prestress was retained to close cracks for fatigue lives above 100, 000 cycles. Prestressed beams failed by bar rupture after concrete crushing in monotonic tests. Abstract: Basalt fibers have recently been introduced as a promising addition to the existing fiber reinforced polymer (FRP) family. A limited amount of information is available on basalt FRP (BFRP) bars and their structural concrete applications. This paper presents the flexural behaviour of sixteen prestressed concrete beams using BFRP bars under monotonic and fatigue loading. The investigated parameters were the level of prestress of the bars (0%, 20% and 40% of their static tension capacity) and the fatigue load ranges. The experimental findings showed that beams with the bars prestressed to 40% of the bar strength had a higher fatigue strength than those prestressed to 0% and 20%. For 40% and 20% prestressed beams, there is no improvement in fatigue performance for load ranges above 20% and 13% of the ultimate capacity of the beams a level at which calculations showed that the remaining prestress did not close cracks at the minimum load in the fatigue load cycle. When compared on the basis of load range versus cycles to failure, the data for the three beam types fell onto a single curve at load levels where the remaining prestress after fatigue creep relaxation no longer closed the crack at the minimum load.